Institutional Histories, Identity Work, and Critical Theory: A Response to Markus Davidsen - Stuckrad, Kocku von (NTT, 2020)
In a response to Markus Davidsen’s article ‘Theo van Baaren’s Systematic Science of Religion Revisited: The Current Crisis in Dutch Study of Religion and a Way Out’, this contribution first reviews Davidsen’s claim of a crisis in the study of religion in the Netherlands, as compared to what he calls the ‘systematic mentality’ of the ‘Nordic countries’. It then turns to the prescribed cure for the alleged ailment that Davidsen develops as an identity work for the study of religion. Over against Davidsen’s attack on postcolonial and gender studies, this article argues for the necessity of critical theory and self-reflection in the academic study of religion. Attempts at uniting the study of religion under one conceptual umbrella are an indication of hegemonic processes that critical theory has rendered untenable. This article concludes that the academic study of religion should be embedded in an interdisciplinary frame of cultural studies.